What Darwin Never Knew and The Botany of Desire (Minneapolis, MN Discover Magazine, 2009)
1. "What Darwin Never Knew" takes on many of the riddles that Darwin couldn't begin to explain and shows how the results of today's scientific research confirms Darwin's insights, while revealing new clues to life's breathtaking diversity in ways the great naturalist could never have imagined. 2. "The Botany of Desire" examines our relationship with the plant world as seen from a unique point of view - the plants. Based on the best-selling book by Michael Pollan, this documentary explains how humans are intricately woven into the web of nature, not standing outside of it. You may have thought that we controlled plants, but you may find that don't give them nearly enough credit. Learn how plants not only shape us, but use humans for their own purposes.
4 hours of content.
Keywords: Charles Darwin -- 1809 - 1882; Documentary. -- Theory of evolution - modern research. -- Plant life. -- Plant and human interaction. -- Science; Scientific discovery